Broadcast news - Brooks, James L. 1940-; Hurt, William 1950-2022 (Criterion Collection, 2010)
A caustic inside look at the Washington news media, stars Holly Hunter in her breakout role, as a feisty television producer torn between an ambitious yet dim anchorman and her closest confidant, a cynical veteran reporter. James L. Brooks' witty, gently prophetic entertainment is a captivating transmission from an era in which ideas on love and media were rapidly changing
Aspect ratio, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: USA 1987
Special features: New, restored high-definition digital transfer; new audio commentary on Brooks career in television and film; deleted scenes and an alternate ending, with commentary by Brooks; new video interview with veteran CBS new producer Susan Zirinsky; featurette containing on-set footage and interviews; original theatrical trailer; booklet featuring an essay by film critic Carrie Rickey
Keywords: Broadcast journalism / Washington (D.C.) / Drama; Television journalists / Washington (D.C.) / Drama; Women television producers and directors / Washington (D.C.) / Drama; Triangles (Interpersonal relations) / Drama; Triangles (Interpersonal relations) -- Drama.; Women television producers and directors -- Washington (D.C.) -- Drama.; Television journalists -- Washington (D.C.) -- Drama.; Broadcast journalism -- Washington (D.C.) -- Drama.; Feature films.; Comedy films.; Dreierbeziehung; Regisseurin; Fernsehen; Rundfunk; Liebesfilm; Washington (D.C.) / Drama; Washington, DC; Film; DVD-Video